Tektualitas Sejarah dalam Mati Baik-Baik, Kawan - Yeni Yulianti (Balai Bahasa Kalimantan Barat, 2019)
This research reviews the 1965 Tragedy in the collection of short stories Mati Baik-Baik, Kawan (MBBK) by Martin Aleida using New Historicism perspective. The New Historism allows us to answer questions of textuality of history in MBBK. New Historicism has been applied as a theoretical framework asserting that literary pieces cannot be separated from political, social, and economic praxis. The theory is based on three basic assumptions: 1) that every expressive act is embedded in a network of material practices; 2) literary and nonliterary texts circulate inseparably; 3) no discourse, imaginative or archival, gives acces to unchanging truths nor expresses inalterable human nature. The research applied parrarel reading method involving literary and nonliterary texts. Any efforts to analyze the textuality of history in the research is to assess the texts in the collection of short stories MBBK through exposure of the 1965 Tragedy. The finding of research of textuality of history of the 1965 tragedy in MBBK put stress upon post impact of G30S such as human right abuse against victims.